SLE stratification based on BAFF and IFN-I bioactivity for biologics and implications of BAFF produced by glomeruli in lupus nephritis. (12th September 2022) - Itotagawa, Eri; Tomofuji, Yoshihiko; Kato, Yasuhiro; Konaka, Hachiro; Tsujimoto, Kohei; Park, JeongHoon; Nagira, Daiki; Hirayama, Takehiro; Jo, Tatsunori; Hirano, Toru; Morita, Takayoshi; Nishide, Masayuki; et al.
Abstract: Objective: B-cell activating factor (BAFF) is implicated in SLE pathogenesis. Blocking BAFF signalling has contributed to reducing glucocorticoid dosage and preventing organ damage. However, clinical characteristics of patients who may benefit from this therapy are not yet fully elucidated. Therefore, we identified patients with high BAFF-bioactivity to investigate their clinical characteristics and BAFF-producing cells. Methods: We established the reporter cell for BAFF and investigated the clinical characteristics of SLE patients with high BAFF-bioactivity. We identified BAFF-expressing kidney cells using publicly available scRNA-seq data and immunohistological analysis. SLE patients were stratified based on the bioactivity of BAFF and type-I IFN (IFN-I) to identify associated characteristic clinical manifestations. Results: SLE patients, especially patients with LN, had significantly higher serum BAFF-bioactivity than healthy controls (HC) and non-LN patients. Additionally, single-cell-RNA-seq data and immunohistological analysis of kidney samples from LN patients revealed that BAFF is expressed in glomerular macrophages and mesangial cells. Notably, BAFF bioactivity was elevated in the urine of LN patients compared with that of non-LN patients, while no IFN-I bioactivity was detected in the urine. Furthermore, SLE stratification based on bioactivities of serum BAFF and IFN-I revealed the clinical characteristics of patients: high BAFF represented patients with LN and high IFN-I represented patients with blood and skin manifestations. Conclusions: Monitoring urinary BAFF-bioactivity may be valuable in diagnosing LN. Furthermore, stratification based on serum BAFF and IFN-I bioactivities may allow the identification of appropriate patients for biologics targeting BAFF and IFN-I.